2021
DOI: 10.1136/gutjnl-2021-324243
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of non-invasive tests for advanced fibrosis in patients with NAFLD: an individual patient data meta-analysis

Abstract: ObjectiveLiver biopsy is still needed for fibrosis staging in many patients with non-alcoholic fatty liver disease. The aims of this study were to evaluate the individual diagnostic performance of liver stiffness measurement by vibration controlled transient elastography (LSM-VCTE), Fibrosis-4 Index (FIB-4) and NAFLD (non-alcoholic fatty liver disease) Fibrosis Score (NFS) and to derive diagnostic strategies that could reduce the need for liver biopsies.DesignIndividual patient data meta-analysis of studies ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
239
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 272 publications
(307 citation statements)
references
References 82 publications
8
239
2
10
Order By: Relevance
“…After multivariate analysis, the model included age, BMI, AST/ALT ratio, platelet count, hyperglycaemia and albumin as significant factors. The proposed formula is shown [ 110 ] in the equation: NFS = −1.675 + 0.037 × age (years) + 0.094 × BMI (kg/m 2 ) + 1.13 × impaired fasting glycemia (IFG) or diabetes (yes = 1, no = 0) + 0.99 × AST/ALT ratio − 0.013 × platelet (×109/L) − 0.66 × albumin (g/dL). A score below −1.455 would be inconsistent with significant fibrosis, whilst a score above 0.676 can diagnose advanced fibrosis.…”
Section: Biochemical Diagnostic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…After multivariate analysis, the model included age, BMI, AST/ALT ratio, platelet count, hyperglycaemia and albumin as significant factors. The proposed formula is shown [ 110 ] in the equation: NFS = −1.675 + 0.037 × age (years) + 0.094 × BMI (kg/m 2 ) + 1.13 × impaired fasting glycemia (IFG) or diabetes (yes = 1, no = 0) + 0.99 × AST/ALT ratio − 0.013 × platelet (×109/L) − 0.66 × albumin (g/dL). A score below −1.455 would be inconsistent with significant fibrosis, whilst a score above 0.676 can diagnose advanced fibrosis.…”
Section: Biochemical Diagnostic Markersmentioning
confidence: 99%
“…Therefore, with this model, only the patients with indeterminate results, i.e., 25% of patients, would require a liver biopsy. In a meta-analysis of 37 studies, Mózes et al reported the AUROC of NFS to be 0.73 [ 110 ]. One of the main limitations of the test is how BMI might be interpreted differently in different ethnic groups.…”
Section: Biochemical Diagnostic Markersmentioning
confidence: 99%
“…However, a key disadvantage is its propensity to overestimate fibrosis in alcohol users, due to its heavy reliance on AST [ 95 ]. Nonetheless, FIB-4 has been found to increase sensitivity of fibrosis detection and decrease the needs for liver biopsies, especially when combined with imaging-based biomarkers, such as liver stiffness measurement (LSM) detected by acoustic resonance form impulse (ARFI) and vibration controlled transient elastography (VCTE) [ 96 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Moreover, studies have shown that these systems may avoid up to 38-80% of liver biopsies (29,30). Currently, no single marker has been used for the precise detection of MAFLD/NAFLD, as isolated biomarkers do not provide sufficiently accurate information for diagnosis (31)(32)(33). However, when coupled with clinical features and with each other, accurate diagnosis, staging, and prognosis for this disease become possible (34).…”
Section: Introductionmentioning
confidence: 99%